Correlation of EGFR, RAS, ERK and Ki-67 as predictor of inverted papilloma malignancy transformation - Sonny Soebjanto; Pudji Rahayu; Hendradi Surjotomo; Aris Satria Hardika (PERHATI-KL, 2020)
ABSTRACTBackground: Inverted papilloma (IP) is benign tumor of the nasal cavity and paranasal sinuses epithelium. Sinonasal squamous cell carcinoma (SCC) is epithelial malignancy of nasal cavity and paranasal sinuses. HPV increases epidermal growth factor receptor (EGFR) expression mediated by E5. RAS is part of the RAS-RAF-MEK-ERK pathway that regulates various cell functions. Ki-67 serves as a molecular marker of tumor proliferation. Early malignant transformation often goes unnoticed. It is important to know the roles of EGFR, RAS, ERK and Ki-67 as predictor for tumor markers in IP and Sinonasal SCC. Objective: To find out the correlation of EGFR, RAS, ERK expressions towards Ki-67 expression as predictor of sinonasal IP transformation into sinonasal SCC. Method: A cross sectional study taking samples from the medical record of Dr.Saiful Anwar Hospital. The expression of EGFR, RAS, ERK and Ki-67 were examined with immunohistochemistry. Result: The estimated inner model results for direct influence of EGFR, RAS, ERK and Ki-67 towards IP and SCC were 2.352, 2.019, 2.625, and 2.213. The estimated inner model results for direct influence of EGFR, RAS and ERK towards Ki- 67 were 2.386, 3.811, and 3.00. Discussion: Previous research had reported an increase in Ki-67 index indicated the role of Ki-67 in cell tranformation of IP with dysplasia into SCC. Conclusion: EGFR, RAS and ERK expressions related to Ki-67 on IP and SCC. Increased expressions of EGFR, RAS, ERK and Ki-67 on IP indicated risk of malignant transformation. EGFR, RAS, ERK and Ki-67 could become predictors of IP transformation into SCC. ABSTRAKLatar belakang: Papiloma inverted (PI) merupakan tumor jinak epitel kavum nasi dan sinus paranasal. Karsinoma sel skuamosa (KSS) sinonasal merupakan keganasan yang berasal dari epitel mukosa kavum nasi dan sinus paranasal. HPV meningkatkan ekspresi EGFR yang dimediasi oleh E5. RAS merupakan bagian dari jaras RAS–RAF–MEK–ERK yang mengatur berbagai fungsi sel. Ki-67 berfungsi sebagai penanda molekuler proliferasi tumor. Diagnosis dini transformasi keganasan pada papiloma inverted seringkali luput dari pengamatan. Penting mengetahui peran EGFR, RAS, ERK dan Ki-67 sebagai cikal bakal penanda tumor pada IP dan KSS sinonasal. Tujuan: Mengetahui hubungan ekspresi EGFR, RAS, ERK terhadap Ki-67 sebagai prediksi transformasi keganasan PI sinonasal menjadi KSS sinonasal. Metode: Penelitian cross sectional, sampel penelitian diambil dari arsip rekam medis rawat jalan yang masih didapatkan preparat histopatologi papiloma inverted dan karsinoma sel skuamosa sinonasal di laboratorium Patologi Anatomi, dan dilakukan pemeriksaan ekspresi EGFR, RAS, ERK dan Ki-67 dengan imunohistokimia. Hasil: Hasil estimasi inner model untuk pengaruh langsung EGFR, RAS, ERK dan Ki-67 terhadap PI dan KSS sebesar 2,352, 2,019, 2,625 dan 2,213. Hasil estimasi inner model untuk pengaruh langsung EGFR, RAS dan ERK terhadap Ki-67 sebesar 2,386, 3,811 dan 3,00. Diskusi: Penelitian terdahulu membuktikan peningkatan indeks Ki-67 merupakan pertanda adanya peran Ki-67 pada perubahan PI dengan displasia menjadi SCC. Kesimpulan: Ekspresi EGFR, RAS dan ERK berhubungan terhadap Ki-67 pada IP dan KSS. Peningkatan ekspresi EGFR, RAS, ERK dan Ki-67 pada PI menandakan adanya risiko terjadi transformasi keganasan. EGFR, RAS, ERK dan Ki-67 dapat menjadi cikal bakal prediktor transformasi keganasan PI menjadi KSS.